Economic performance of smallholder exotic dairy cattle in the marginal zones of Kenya - Kavoi, Mutuku Muendo, author; Hoag, Dana L., advisor; Pritchett, James G., committee member; Davies, Stephen P., committee member; Wailes, William R., committee member (Colorado State University. Libraries, 2007)
Kenya's dairy experts in 1970s argued that the "dry marginal zones" could not meet the requirements of the high performing exotic breeds. They recommended the use of upgraded indigenous breeds which have a lower nutritive requirements and greater adaptability even though their milk supply response capability is relatively low. Yet, smallholder farmers have defied expert advice and have instead shown preference for high exotic grade breeds as a key component of their improved milk production strategies. Does this imply that exotic breeds are more profitable than the indigenous breeds? Experts base their advice on research in the high potential zones, not on marginal zones. The common use of exotic breeds by local farmers in the marginal zones provides an opportunity for an applied research project to compare the performance of these two types of cattle breeds. Data on dairy farm operations for the period July 2005 to June 2006 is collected and analysed. Three different methodological approaches are applied to determine the performance of dairy farms; (i) stochastic cost frontier to determine economic efficiency; (ii) translog cost function-input demand systems; and, (iii) translog profit function-input demand systems were used to determine various elasticitis and important details on production systems such as input substitutions and economies of scale. The results indicate that exotic breeds performed better than indigenous breeds: The large breeds have the lowest cost inefficiency. Overall, the mean cost inefficiency of dairy production in the marginal zones is 27.45 %. The resource use inefficiency is significantly explained by institutional and socio-economic factors with varying marginal impacts of the respective variables. The internal workings of the production and marketing systems shows that dairy farmers maximize profits and that there are no constant returns to scale. Most of the dairy inputs are complements and the dairy establishment faces diseconomies of scale. The supply response analysis indicates that institutional and socio-economic factors have much greater elastic impacts on dairy production than the price factors. In sum, a further liberalization of the dairy sector would be beneficial to stimulate supply response. However, institutional and socio-economic setups such as road infrastructure, extension services, dairy records, credit and education which have a greater impact are required to enhance resource use efficiency and reinforce the liberalization policy. This implies that judicious investments in institutional and socio-economic factors through enhancement of public expenditure are required to promote market oriented smallholder dairy in the marginal zones.
Keywords: farmers; dairy farms; cattle; nutrition; adaptability; stochastic models; socioeconomic factors; studies; agriculture; households